2001
DOI: 10.1348/135532501168253
|View full text |Cite
|
Sign up to set email alerts
|

Underlying dimensions in young people's attitudes towards police weaponry in England: Some experiential influences from criminal victimization and police contact

Abstract: Purpose. This study examines the influence of experiential variables, such as reported contacts with the police, upon attitudes towards the use of police weaponry in England and Wales. Method. A factor analysis (N = 605) of response to a specially developed questionnaire led to the identification of five underlying dimensions of public attitudes towards police weaponry. Further analyses explored the role of demographic and experiential variables in these attitudes. Results. Neither age nor sex were found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous research has consistently demonstrated that public confidence in the justice system is determined, in large part, by trust in police. For example, trust in police is an important predictor of public attitudes to police weaponry in the United Kingdom (Cooke, Puddifoot, & Brown, 2001). When citizens trust police, they are more likely to perceive police authority as legitimate, and thus more likely to cooperate with authorities and comply with the law (Sunshine & Tyler, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has consistently demonstrated that public confidence in the justice system is determined, in large part, by trust in police. For example, trust in police is an important predictor of public attitudes to police weaponry in the United Kingdom (Cooke, Puddifoot, & Brown, 2001). When citizens trust police, they are more likely to perceive police authority as legitimate, and thus more likely to cooperate with authorities and comply with the law (Sunshine & Tyler, 2003).…”
Section: Introductionmentioning
confidence: 99%